2015
DOI: 10.1002/ajmg.a.36881
|View full text |Cite
|
Sign up to set email alerts
|

A family of distal arthrogryposis type 5 due to a novel PIEZO2 mutation

Abstract: Distal arthrogryposis (DA) encompasses a heterogeneous group of hereditary disorders with multiple congenital contractures predominant in the distal extremities. A total of 10 subtypes are proposed based on the pattern of contractures and association with extraarticular symptoms. DA5 is defined as a subtype with ptosis/oculomotor limitation. However, affected individuals have a variety of non-ocular features as well. We report on a two-generation family, including four affected individuals who all had congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…We previously reported that a subtype of distal arthrogryposis type 5 (DA5) is caused by autosomal dominant mutations of PIEZO2 with slower inactivation kinetics than the wild-type channel 37 . Most patients with DA5 suffer from joint contractures and develop restrictive lung diseases 37,38 . Our data raise the possibility that overactivation of PIEZO2 + vagal neurons might overtly increase lung stretch responses in these patients and lead to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a subtype of distal arthrogryposis type 5 (DA5) is caused by autosomal dominant mutations of PIEZO2 with slower inactivation kinetics than the wild-type channel 37 . Most patients with DA5 suffer from joint contractures and develop restrictive lung diseases 37,38 . Our data raise the possibility that overactivation of PIEZO2 + vagal neurons might overtly increase lung stretch responses in these patients and lead to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…Over a dozen mutations in Piezo2 are associated with several arthrogryposis disorders (Table 1) [3941]. Two of these mutations have been electrophysiologically characterized and destabilize inactivation, leading to an overall increase of calcium influx [40].…”
Section: Physiology Of Piezo Mechanotransductionmentioning
confidence: 99%
“…When Piezo2 was ablated in these cells using CRISPR/Cas9 technology, mechanically activated currents were abolished. Along with directly demonstrating that Piezo2 is necessary for mechanotransduction in human LTMRs, this study opens up new avenues for analyzing and genetically correcting, disease-causing Piezo2 mutations in human cell types [22,33,34]. …”
Section: Piezo2 Pushes To the Forefront Of Mechanosensory Transductionmentioning
confidence: 99%